Poking facebook: characterization of osn applications - Gjoka, Minas; Markopoulou, Athina; Sirivianos, Michael (My University, 2008)
Facebook is one of the most popular Internet sites today. A key feature that arguably contributed to Facebook's unprecedented success is its application platform, which enables the development of third-party social-networking applications. Understanding how these applications are installed and used is important for the function and utility of web-based online social networks, e.g. to better engineer them and/or to design advertising campaigns. In this paper, we characterize the popularity and user reach of Facebook applications. We analyze application usage data gathered over a period of six months from Facebook and Adonomics - a Facebook analytics service. We also crawl publicly accessible Facebook user profiles and obtain per-user application installation statistics, for approximately 300K users and 13.6K applications. Our findings include that (i) the popularity of Facebook applications has a highly skewed distribution; (ii) although the total number of application installations increases with time, the average user activity decreases; and (iii) users with more applications installed are more likely to install new applications
Keywords: Online social networks; Computer science; Internet